Measuring coral disease lesions: a comparison of methodologies - Neely, Karen L. (Frontiers in Marine Science, 2024)
The presence of stressors, particularly disease, on corals necessitates assessments of their severity in order to compare threat levels and to plan for impacts. Diseases in particular are often measured via the rate at which a lesion moves across a coral (lesion progression rate) to determine the impact of those lesions and also to compare virulence across species, regions, and disease types. Lesion progression can even be used as a field indicator for disease identification. Many different methodologies have been used to measure lesion progression rates. These may be field-based or photographic measurements, and they include linear progression rates as well as areal progression rates. All methods have pros and cons, including varying levels of accuracy and repeatability, variability with respect to colony and lesion sizes, and time and computational requirements. Additionally, not all metrics can be directly compared, and so experiments done with the intent to compare with previous work must consider methodologies used in former studies. Areal progression rates have high variability, but can provide impressive information on overall tissue loss. Overall, linear lesion progression rates provide more accurate and less variable assessments of loss, and are better used for comparisons. Using the average of multiple linear measurements may further increase precision. Measuring from photographs rather than direct field measurements provides a more permanent and repeatable record, but outside of directly planar surfaces is likely to yield inaccuracies. The emerging use of 3-D photogrammetry can overcome many of these limitations, but the methods require considerable time and computational power. The pros and cons of each methodology should be assessed during experimental design to best answer the hypotheses in question as well as consider whether comparisons to other studies are valid.